ISLAM, PSIKOLOGI, DAN KEBIJAKAN PUBLIK: ANALISIS TERHADAP PENGESAHAN UU TPKS - Agnes Nor Febria; Ahmad Fauzi (KOLABORATIF: Jurnal Isu Sosial dan Tinjauan Kebijakan, 2023)
This article aims to analyze the UU TPKS from the perspective of Islamic law and a psychological approach also public policy. This research is library research by using data collection tools from articles, journals, books that was contained in Google Scholar. The data analysis technique uses a content analysis approach in the UU TPKS. The findings of this study suggest that a leader has a duty to guard his followers' souls, minds, dignity, and worth in Islam. According to QS. Ar-Rum (30):21, Islam condemns the use of force in the display of love and affection for women. Islam forbids violence against women. A leader must develop a rule to prevent sexual assault on women and advance moral values as a means of holding his people accountable. This rule must be followed and put into action by all members of society, as stated in (QS. An-Nisa, (04): 59. In addition to taking a religiously based approach, leaders are heavily influenced by modern science, such as psychology, when formulating policies for the welfare of their people, particularly women.